The Digitalization of Education and Implication for the 21th Century Skills of The Millenial Moslem Generation - Muttaqin, Imron (Al-Mudarris, 2022)
The sophistication of information technology has changed the educational model to become anti-establishment related to scientific authority, material literacy, time and place for religious learning. All knowledge is available on internet seem perfect and good. This study is library research aimed to describe the experience of the millennial moslem generation. The findings inform three critical points; first, the interaction process with the digital sources has imply for reducing the critical power of problem-solving. Second, The intensity in the digital world of seeking information makes communication styles changed, and third, digital education led limitedinteraction and collaboration. For further researcher are suggested to conduct study on strategies or methods to get authoritative sources for religious literature for students.